Effective business strategy: a case study of Tutti Frutti (M) Sdn Bhd / Hazlee Shah Shukor - Shukor, Hazlee Shah (Faculty of Business and Management, 2009)
This research was carried out to determine the effectiveness of Tutti Frutti’s business strategy upon the establishment of their first yogurt shop. This research will be focusing in three purposes which are understanding the business strategy used by the company, determine the effectiveness of the company’s business strategy and to give recommendation which could benefits the company in the future. Upon the obtaining of information, the researcher held a series of interviews with the company’s General Manager and the Operations Manager as well as self-observation. Gathering internet resources, articles, journals and books also helped the researcher to compare between the company’s practices and the theory stated in the book. The study showed that there is a minor gap after all the information had been analyzed. In conclusion, Tutti Frutti is using the franchising strategy to promote or market its product and has practiced an effective business strategy. However, the minor gap showed that the company should improve on certain area to enhance its business operations such as creating a reasonable time frame for the task given to the staff as well as the hiring of local designer instead of foreign designer.